Changes in the Equity of the Long-Term Care System in Korea Based on Coulter Index Differences for the Years 2000, 2008, and 2015. Issue 1 (2nd January 2022) - Kim, Sejin; Chae, Joosuk; Nam, Seok In
ABSTRACT: In this study, we examined the adequacy of supply and demand under private expansion of the long-term care (LTC) infrastructure after the introduction of long-term care insurance (LTCI) for the older people in Korea. We used Coulter's coefficient of inequality (Coulter index) to analyze the equity of LTC services by region. In addition, we analyzed the trend of equity changes through equity analysis for three time points: 2000, 2008, and 2015. We found that the level of inequity in LTC service infrastructure in Korea is lower in 2015 compared with 2000, but the differences among regions are high. The adjustment factors in 2015 showed prominent shortages of facilities in urban areas and oversupply in suburban areas. Based on these results, we propose an LTC service infrastructure that meets the demand and improves service access according to regional characteristics.